Methodologies and tools of risk management: Hurricane risk index (HRi). (October 2018) - Hernández, M.L.; Carreño, M.L.; Castillo, L.
Abstract: Mexico is recognized worldwide for the extension of its coastlines and its tourist exploitation. Quintana Roo is one of the Mexican states, which has a shoreline of approximately 800 km, known as the Mexican Caribbean. The hurricanes that form in the Atlantic Ocean are the main natural hazard to which this region is exposed. In this article, hurricane risk is evaluated for coastal cities through the definition of a system of indicators. Based on this indicators system, the Hurricane Risk Index ( HRi ) is calculated. This system allows the construction of vulnerability indices for different dimensions: physical, environmental, social, economic, cultural and institutional. The obtained results can contribute to the definition of public prevention policies and actions to reduce the levels of vulnerability and increase the resilience of these communities. This indicators model is applied to two coastal cities of the Mexican Caribbean; Mahahual, obtaining an HRi of 82.13%, and Chetumal obtaining an HRi of 69.31%, corresponding to the impact of Hurricane Dean in 2007. The proposed indicators system can be replicated for different hazards.